Nomenclature notes on some orthoclads (Diptera: Chironomidae) - Sæther, O. A.; Ferrington Jr., L. C. (Zootaxa, 2003)
New nomenclatorial acts are proposed for chironomids in anticipation of publication on the Fauna Europaea, a database of the scientific names and distribution of all living multicellular European land and fresh-water animals. Thienemanniella caspersi Sæther is proposed as a new replacement name for Th. similis Caspers & Reiss, 1989. Five new generic combinations are given: Dactylocladius albipennis Goetghebuer, 1921, Orthocladius (Dactylocladius) brevifurcatus Edwards, 1926, and Lindebergia bothnica Tuiskunen, 1984 are transferred to Pseudosmittia Goetghebuer; while Smittia lacunarum Goetghebuer, 1931 and Smittia (Pseudosmittia) terrestris Goetghebuer , 1943 are both transferred to Bryophaenocladius Thienemann. Twenty-two new synonyms are given: Pseudosmittia amamibifurca Sasa, 1990 is a junior synonym of Pseudosmittia mathildae Albu, 1968; Pseudosmittia antillaria Sæther, 1981 of Pseudosmittia forcipata (Goetghebuer, 1921); Pseudosmittia arenaria flava Strenzke, 1960 of Pseudosmittia arenaria Strenzke, 1960; Smittia avicularia Goetghebuer, 1950 of Pseudosmittia trilobata (Edwards, 1929); Smittia brachyptera Goetghebuer, 1934 of Pseudosmittia conjuncta (Edwards, 1929); Pseudosmittia brevitarsis Brundin, 1947, Pseudosmittia kurobaokasia Sasa & Okazawa, 1992, Smittia oxoniana Edwards, 1937 not Edwards, 1922, and Pseudosmittia schachti Caspers & Reiss, 1989 of Pseudosmittia ruttneri Strenzke & Thienemann, 1942; Spaniotoma (Smittia) curticosta Edwards, 1929 of Pseudosmittia albipennis (Goetghebuer, 1921); Smittia hamata Freeman, 1956 of Pseudosmittia danconai (Marcuzzi, 1947); Pseudosmittia linguata Caspers & Reiss, 1989 of Pseudosmittia nishiharaensis Sasa & Hasegawa, 1988; Smittia longitibia Goetghebuer, 1933 and Pseudosmittia mediocarinata Caspers & Reiss, 1989 of Pseudosmittia nanseni (Kieffer, 1926); Spaniotoma (Smittia) recta Edwards, 1929 and Pseudosmittia togarisea Sasa & Okazawa, 1992 of Pseudosmittia oxoniana (Edwards, 1922); Spaniotoma (Smittia) scotica Edwards, 1929, Pseudosmittia togasitea Sasa & Pseudosmittia triplex Strenzke, 1950 is a valid species and not a synonym of P. forcipata (Goetghebuer, 1921) as stated in Ashe & Cranston (1990). Pseudosmittia virgo montana Strenzke, 1950 is raised to species level as Pseudosmittia montana. The following names are nomina dubia: Camptocladius flaviventris Kieffer, 1921, Camptocladius hexalobus Kieffer, 1924, Camptocladius longicrus Kieffer, 1921, Pseudosmittia restricta Brundin, 1956, Smittia (Pseudosmittia) tenebrosa Goetghebuer, 1943, Camptocladius trifoliatus Kieffer, 1924, Smittia (Pseudosmittia) vicana Goetghebuer, 1943.